Solid-liquid double-state luminescent material with high quantum yield as well as preparation and application of solid-liquid double-state luminescent material

The preparation of boron-doped carbon nitride quantum dots through solid phase reaction of boron oxide and carbon nitride quantum dots solves the shortcomings of CNQDs in long afterglow phosphorescence, and achieves the effects of high quantum yield, long afterglow and rich luminous colors.

CN119463865AActive Publication Date: 2025-02-18SHENZHEN YOUSHENGDA TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411734314.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

When existing carbon nitride quantum dots (CNQDs) achieve long afterglow phosphorescence, there are problems such as short phosphorescence lifetime, single luminous color and low quantum yield, making it difficult to effectively improve optical performance through traditional methods.

Method used

Boron doped carbon nitride quantum dots (BCNQDs) were prepared by solid phase reaction between boron oxide (B2O3) and carbon nitride quantum dots (CNQDs). This material has solid-state liquid dual luminescence performance, improving photoluminescence quantum efficiency and phosphorescence life, and luminous color regulation is achieved.

Benefits of technology

It achieves high quantum yield solid-liquid bi-state luminescence, extends the phosphorescence life, enriches the luminous color, and significantly improves the optical performance of carbon nitride quantum dots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463865A_ABST
    Figure CN119463865A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-liquid double-state luminescent material with high quantum yield and preparation and application thereof, the luminescent material is specifically boron-doped carbon nitride quantum dots (BCNQDs), and the preparation method comprises the steps of preparation of carbon nitride powder, pretreatment of the carbon nitride quantum dots, boron oxide doping and high-temperature solid-phase reaction. The long afterglow material has solid-liquid double-state luminescence and excitation-dependent multicolor luminescence at the same time, and the quantum yield of the long afterglow material is as high as 15.79%. The material presents 15-second afterglow under the excitation of 365nm ultraviolet light, the light-emitting color in the liquid state changes from blue-violet to cyan along with the excitation wavelength, the solid state also has relatively long room-temperature phosphorescence life and afterglow duration, and the fluorescence quantum yield of CNQDs is greatly improved. Due to the excellent performance, the luminescent material can be widely applied to the fields of anti-counterfeiting two-dimensional codes, anti-counterfeiting ink, coded information encryption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a luminescent material, in particular to a high quantum yield boron-doped carbon nitride quantum dot solid-liquid dual-state luminescent material and a preparation method and application thereof. Background Art

[0002] In recent years, room temperature phosphorescent (RTP) materials have attracted much attention due to their wide application potential in anti-counterfeiting and information encryption, bio-imaging and optoelectronic devices. As an emerging zero-dimensional nanomaterial, carbon nitride quantum dots (CNQDs) have gradually become the research focus of RTP materials due to their excellent optical properties, low toxicity and good biocompatibility.

[0003] However, most CNQDs still have problems such as short phosphorescence lifetime, single luminescent color and low quantum yield when achieving long afterglow phosphorescence, which greatly limits their practical applications. Traditionally, researchers extend the afterglow lifetime by embedding quantum dots into rigid matrices to suppress non-radiative transitions, but this method overly relies on the stability of the external environment and it is difficult to effectively improve the optical performance through the internal structure of the material. In addition, most fluorescent materials are usually difficult to achieve solid-liquid dual emission due to aggregation-induced quenching (ACQ) and aggregation-induced emission (AIE) phenomena.

[0004] To improve luminescence and room-temperature RTP performance, existing technologies have attempted to enhance performance by heteroatom doping or introducing defect states, but achieving tunable emission wavelength, high quantum yield, solid-liquid dual emission, and long afterglow lifetime in a single material remains a challenge. Summary of the invention

[0005] In response to the problems in the background technology, the present invention prepared boron-doped carbon nitride quantum dots (BCNQDs) through a solid-phase reaction of boron oxide (B2O3) and carbon nitride quantum dots (CNQDs). Experiments found that the quantum dots are a material that has both solid and liquid dual luminescence properties. The material can effectively improve the photoluminescence quantum efficiency of carbon nitride quantum dots, extend the phosphorescence lifetime, and achieve luminescence color regulation.

[0006] The technical solution adopted by the present invention is: A high quantum yield solid-liquid dual-state luminescent material, the luminescent material is boron-doped carbon nitride quantum dots (BCNQDs), the solid powder of the quantum dots emits bright white light under the irradiation of 365nm ultraviolet lamp; the solid powder is dispersed in water to form a colorless and transparent solution, which exhibits three different colors of fluorescence, blue-purple, dark blue and cyan, respectively, under the irradiation of 265nm, 365nm and 395nm ultraviolet lamps, and presents a 15-second afterglow under the excitation of 365nm ultraviolet light; the quantum dots exhibit a photoluminescence quantum efficiency of up to 15.79% under the excitation of 365nm ultraviolet light.

[0007] Because the boron-doped carbon nitride quantum dots have the advantages of room temperature phosphorescence, long afterglow, solid-liquid dual emission, and rich luminescent colors, they can be used in anti-counterfeiting QR codes, anti-counterfeiting inks, and coded information encryption.

[0008] The present invention also discloses a method for preparing a high quantum yield solid-liquid dual-state luminescent material-boron-doped carbon nitride quantum dots, comprising the following steps: (1) Preparation of carbon nitride powder using melamine as raw material; (2) using the carbon nitride powder prepared in step (1) as a raw material and concentrated nitric acid as a strong oxidant, mixing the two and then oxidizing and refluxing to obtain a mixed solution; (3) diluting the mixed solution obtained in step (2) with deionized water and performing preliminary deacidification treatment using a rotary evaporator; (4) placing the mixed solution that has undergone preliminary deacidification treatment in a quartz boat, placing the quartz boat in a horizontal reaction tube furnace for heating, and further deacidifying by argon gas expulsion to obtain a solid mixture; (5) dissolving the solid mixture of step (4) in deionized water, ultrasonically dispersing, and centrifuging in batches using a high-speed centrifuge, taking the supernatant and ultrasonically dispersing it again to obtain an ultrasonic dispersion; (6) Performing preliminary filtration on the ultrasonic dispersion obtained in step (5) using a 220 nm microporous filter membrane, and then performing secondary filtration on the filtrate using a 25 nm microporous filter membrane; (7) The filtrate obtained by the secondary filtration in step (6) is concentrated, and water is removed by a rotary evaporator for concentration, and then placed in a freeze dryer for freeze drying to obtain fluffy carbon nitride quantum dots with high oxygen functional groups, abbreviated as CNQDs; (8) Grinding the obtained carbon nitride quantum dots and boron oxide mixture thoroughly and placing it in a small porcelain boat, placing it in a quartz tube of a horizontal reaction tube furnace, and performing high-temperature sintering heat treatment under an argon atmosphere; (9) The product sintered in step (8) is ground thoroughly to obtain boron-doped carbon nitride quantum dots, abbreviated as BCNQDs, i.e., solid-liquid dual-state luminescent materials.

[0009] Furthermore, in the preparation method, the step (1) of preparing the carbon nitride powder is to place melamine in a muffle furnace, heat it to 500-600°C at a heating rate of 1°C / min-5°C / min, and calcine it for 2-4h to obtain carbon nitride sintered into a yellow block, and grind the block carbon nitride into powder for later use.

[0010] Furthermore, in the preparation method, the carbon nitride powder in step (2) is mixed with concentrated nitric acid at a solid-liquid ratio of 1 g:100-150 ml, the mass fraction of concentrated nitric acid is 63-68%, the oxidation reflux temperature is 135-150° C., and the reflux time is 24-28 h.

[0011] Furthermore, in the preparation method, the amount of deionized water used in step (3) is 1.5-3 times the volume of the mixed solution of carbon nitride and carbon nitride quantum dots after reflux in step (2), the speed of the rotary evaporator is 60-70 rpm, and the deacidification treatment is carried out in a water bath at 80-90° C. for 3-6 preliminary deacidification treatments.

[0012] Furthermore, in the preparation method, the flow rate of the argon gas in step (4) is 80-100 ml / min, the heating rate of the horizontal reaction tube furnace is 5°C / min, and the temperature is raised to 200-250°C for 3-5h.

[0013] Furthermore, in the preparation method, the power of the ultrasonic machine used for the ultrasonic dispersion in step (5) is 200 W, and the ultrasonic dispersion time is 10-15 min; the centrifugal speed of the centrifuge is 10000-12000 rpm, the time of each centrifugation is 10-20 min, and the centrifugal temperature is 15°C.

[0014] Furthermore, in the preparation method, the rotation speed of the rotary evaporator in step (7) is 60-70 rpm, and freeze drying is performed at -60±10°C for 8-12 hours, and then the water is sublimated according to a set vacuum program. The freezing temperature in the vacuum program is -60±10°C, and the operating time is 60-80 hours.

[0015] Furthermore, in the preparation method, in step (8), the mass ratio of the carbon nitride quantum dots to the boron oxide is 1:1, the flow rate of the argon gas is 60-80 ml / min, the heating rate of the horizontal reaction tube furnace is 5°C / min, and the temperature is raised to 200°C-400°C for sintering heat treatment for 2-5 hours.

[0016] The method of the present invention was used to prepare cyan long-life RTP CNQDs with an emission wavelength of 475nm and an afterglow time of 2.11 seconds. The prepared BCNQDs showed a photoluminescence quantum efficiency of up to 15.79% under 365 nm ultraviolet light excitation, which was significantly improved compared with the quantum efficiency of 0.13% shown by the original CNQDs, indicating that it has broad potential in research and application fields. The excellent performance of BCNQDs in terms of lifetime, afterglow time and quantum efficiency has enabled it to show great application prospects in the fields of anti-counterfeiting and information encryption.

[0017] Due to the adoption of the above technical solution, the beneficial effects of the present invention compared with the prior art are as follows: (1) The present invention uses carbon nitride powder as a precursor, concentrated nitric acid that is easily decomposed by heat as a strong oxidant, and an integrated preparation method of oxidation reflux, ultrasonic stripping and centrifugal stratification, and continuously optimizes the preparation parameters to prepare carbon nitride quantum dots. The obtained product has uniform particle size and morphology, and the size is controllable, generally about 2 to 4 nanometers. It can be dispersed in water to form a colorless and transparent solution, and emits different colors of fluorescence under different ultraviolet lamps. The luminescence is stable and bright, and it is easy to read.

[0018] (2) The present invention prepares boron-doped carbon nitride quantum dots, and the raw materials used are melamine, concentrated nitric acid, and boron oxide, and the auxiliary materials are deionized water and argon. The raw materials are simple and easy to obtain, low in cost, non-toxic and pollution-free, and will not cause harm to the environment and biological health, and are environmentally friendly materials. At the same time, the preparation process is simple, the production cycle is short, and it is suitable for mass production.

[0019] (3) The aqueous solution and solid powder of boron-doped carbon nitride quantum dots prepared by the method of the present invention can be used for anti-counterfeiting identification and multiple information encryption, effectively protecting the authenticity of the product and the safe transmission of information. The solid powder will emit fluorescence of different colors under different ultraviolet lamps. At the same time, after the ultraviolet lamp is turned off, there will be a phosphorescence afterglow phenomenon of up to about 12 seconds. After being dissolved in water, its liquid fluorescence is also excitation-dependent. In the subsequent coding information encryption, product anti-counterfeiting identification and anti-counterfeiting ink applications, it can accurately and effectively identify the information for anti-counterfeiting and perform multiple encryption on the information, thereby ensuring the security and reliability of the information, which can be well applied in life. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a characterization diagram of the intrinsic properties of CNQDs and BCNQDs prepared in Examples 1-3; Among them, a and b are the TEM images and HR-TEM images of CNQDs, respectively; c, d are TEM and HR-TEM images of BCNQDs400 (Example 1), respectively; e, f, and g are the FT-IR, UV-vis, and XPS spectra of CNQDs and BCNQDs, respectively.

[0021] Figure 2 is a photophysical property diagram of BCNQDs prepared in Examples 1-3; Wherein, a, b, and c are the fluorescence excitation spectrum, fluorescence emission spectrum, and phosphorescence emission spectrum of BCNQDs200 (Example 2), BCNQDs300 (Example 3), and BCNQDs400 (Example 1), respectively; d, e, and f are the normalized fluorescence and phosphorescence spectra of BCNQDs200 (Example 2), BCNQDs300 (Example 3), and BCNQDs400 (Example 1) under excitation at 300 nm, 365 nm, and 365 nm, respectively; g is the time-resolved afterglow decay and fitting curves of BCNQDs under excitation at 470 nm (BCNQDs200), 507 nm (BCNQDs300) and 520 nm (BCNQDs400); h is the CIE coordinate diagram of BCNQDs; i is the fluorescence spectrum of BCNQDs400 (Example 1) under excitation at 265 nm, 365 nm and 395 nm, and the inset shows the CIE coordinate diagram of the corresponding emission peak and the morphology of the aqueous solution in the cuvette.

[0022] Figure 3 is a photophysical excitation dependence characteristic diagram of BCNQDs400 prepared in Example 1; Among them, a, b, and c are the solid-state fluorescence, solid-state phosphorescence, and liquid-state fluorescence emission spectra of BCNQDs400 under different excitations, respectively; d, e, and f are the normalized emission spectra of solid-state fluorescence, solid-state phosphorescence, and liquid-state fluorescence of BCNQDs400 under different excitations, respectively.

[0023] Figure 4 It is a schematic diagram and a real picture of the application of BCNQDs prepared in Examples 1-3 in anti-counterfeiting and information encryption; Wherein: a is the corresponding photographs of BCNQDs200 (Example 2), BCNQDs300 (Example 3) and BCNQDs400 (Example 1) powders under sunlight, 365 nm ultraviolet light and stopped excitation; b is the information encryption system based on three different temperature ratios of BCNQDs; c is the application design of BCNQDs400 in liquid anti-counterfeiting. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the present application, a clear and complete description of the technical solution of the present application is given below in conjunction with the drawings and embodiments. Of course, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Example

[0025] A method for preparing a high quantum yield solid-liquid dual-state luminescent material-boron-doped carbon nitride quantum dots, comprising the following steps: (1) Weigh 10 g of melamine and place it in a small porcelain boat. Then, invert another small porcelain boat on top of it and wrap it with tin foil. Place it in a muffle furnace and heat it to 500 °C at a heating rate of 5 °C / min for 3 h to obtain carbon nitride sintered into yellow blocks. Grind the block carbon nitride into powder for later use. (2) Using the ground carbon nitride powder in step (1) as a raw material, using concentrated nitric acid with a mass fraction of 68% as a strong oxidant, taking 5g of carbon nitride powder and 500ml of concentrated nitric acid at a solid-liquid ratio of 1g:100ml, mixing the two, and then refluxing them in a 1000ml round-bottom flask at 140°C for 24h to obtain a mixed solution; (3) diluting the mixed solution obtained in step (2) with 1000 ml of deionized water, and performing preliminary deacidification treatment using a rotary evaporator at a speed of 70 rpm. The deacidification treatment was performed in a water bath at 80° C. for three times; (4) The mixed solution after preliminary deacidification is placed in a quartz boat, and the quartz boat is placed in a horizontal reaction tube furnace, and heated at 230°C for 3 hours, and further deacidified by argon gas expulsion to obtain a mixed solid of carbon nitride and carbon nitride quantum dots, wherein the flow rate of argon gas is 80 ml / min, and the heating rate of the horizontal reaction tube furnace is 5°C / min; (5) The solid mixture obtained in step (4) was dissolved in deionized water, and ultrasonically dispersed for 15 min using an ultrasonic machine with a power of 200 W, and centrifuged in batches at a high-speed centrifuge of 12,000 rpm for 15 min, and the supernatant was ultrasonically dispersed again for 15 min, wherein the centrifugation temperature was 15°C; (6) using a 220 nm microporous filter membrane to perform preliminary filtration on the ultrasonic dispersion obtained in (5), and then using a 25 nm microporous filter membrane to perform secondary filtration on the filtrate; (7) The filtrate obtained by the secondary filtration in step (6) is concentrated by removing water using a rotary evaporator at a rotation speed of 70 rpm, and then placed in a freeze dryer for freeze drying to obtain fluffy carbon nitride quantum dots with high oxygen functional groups, abbreviated as CNQDs, wherein the freezing step is frozen at -70°C for 8 hours, and the vacuum step is operated at a freezing temperature of -70°C for 72 hours; (8) The carbon nitride quantum dots and boron oxide obtained in step (7) were mixed in a mass ratio of 1:1, ground thoroughly, and placed in a small porcelain boat, which was placed in a quartz tube of a horizontal reaction tube furnace. The boat was sintered at 400°C for 3 h under an argon atmosphere, wherein the argon flow rate was 80 ml / min and the heating rate of the horizontal reaction tube furnace was 5°C / min; (9) The sintered product is ground thoroughly to obtain boron-doped carbon nitride quantum dots, denoted by BCNQDs400 (the number indicates the sintering temperature), which is a solid-liquid dual-state luminescent material. Example 2

[0026] A method for preparing a high quantum yield solid-liquid dual-state luminescent material-boron-doped carbon nitride quantum dots, comprising the following steps: (1) Weigh 10 g of melamine and place it in a small porcelain boat. Then, invert another small porcelain boat on top of it and wrap it with tin foil. Place it in a muffle furnace and heat it to 500 °C at a heating rate of 3 °C / min for 4 h to obtain carbon nitride sintered into yellow blocks. Grind the block carbon nitride into powder for later use. (2) Using the ground carbon nitride powder in step (1) as a raw material, using 68% concentrated nitric acid as a strong oxidant, taking 5 g of carbon nitride powder and 600 ml of concentrated nitric acid at a solid-liquid ratio of 1 g:120 ml, mixing the two, and then refluxing them in a 1000 ml round-bottom flask at 135° C. for 36 hours to obtain a mixed solution; (3) diluting the mixed solution obtained in step (2) with 1500 ml of deionized water, and performing preliminary deacidification treatment using a rotary evaporator at a speed of 60 rpm. The deacidification treatment was performed in a water bath at 90° C. for 5 times; (4) The mixed solution after preliminary deacidification is placed in a quartz boat, and the quartz boat is placed in a horizontal reaction tube furnace, and heated at 200°C for 4 hours, and further deacidified by argon gas expulsion to obtain a mixed solid of carbon nitride and carbon nitride quantum dots, wherein the flow rate of argon gas is 90 ml / min, and the heating rate of the horizontal reaction tube furnace is 5°C / min; (5) The solid mixture obtained in step (4) was dissolved in deionized water, and ultrasonically dispersed for 10 min using an ultrasonic machine with a power of 200 W, and centrifuged in batches at a high-speed centrifuge of 12,000 rpm for 10 min. The supernatant was ultrasonically dispersed again for 10 min, wherein the centrifugation temperature was 15°C; (6) using a 220 nm microporous filter membrane to perform preliminary filtration on the ultrasonic dispersion obtained in (5), and then using a 25 nm microporous filter membrane to perform secondary filtration on the filtrate; (7) The filtrate obtained by the secondary filtration in step (6) is concentrated by removing water using a rotary evaporator at a rotation speed of 60 rpm, and then placed in a freeze dryer for freeze drying to obtain fluffy carbon nitride quantum dots with high oxygen functional groups, abbreviated as CNQDs, wherein the freezing step is frozen at -50°C for 8 hours, and the vacuum step is operated at a freezing temperature of -50°C for 60 hours; (8) The carbon nitride quantum dots and boron oxide obtained in step (7) were mixed in a mass ratio of 1:1, ground thoroughly, and placed in a small porcelain boat, which was placed in a quartz tube of a horizontal reaction tube furnace. The mixture was sintered at 200°C for 3 h under an argon atmosphere, wherein the argon flow rate was 60 ml / min and the heating rate of the horizontal reaction tube furnace was 5°C / min; (9) The sintered product is ground thoroughly to obtain boron-doped carbon nitride quantum dots, denoted by BCNQDs200 (the number indicates the sintering temperature), which is a solid-liquid dual-state luminescent material. Example 3

[0027] A method for preparing a high quantum yield solid-liquid dual-state luminescent material-boron-doped carbon nitride quantum dots, comprising the following steps: (1) Weigh 10 g of melamine and place it in a small porcelain boat. Then, invert another small porcelain boat on top of it and wrap it with tin foil. Place it in a muffle furnace and heat it to 600 °C at a heating rate of 4 °C / min for 2 h to obtain carbon nitride sintered into yellow blocks. Grind the block carbon nitride into powder for later use. (2) Using the ground carbon nitride powder in step (1) as a raw material, using 68% concentrated nitric acid as a strong oxidant, taking 5 g of carbon nitride powder and 750 ml of concentrated nitric acid at a solid-liquid ratio of 1 g:150 ml, mixing the two, and then oxidizing and refluxing them in a 1000 ml round-bottom flask at 150° C. for 48 hours to obtain a mixed solution; (3) diluting the mixed solution obtained in step (2) with 2000 ml of deionized water, and performing preliminary deacidification treatment using a rotary evaporator at a speed of 65 rpm. The deacidification treatment was performed in a water bath at 85° C. for 6 times; (4) The mixed solution after preliminary deacidification is placed in a quartz boat, and the quartz boat is placed in a horizontal reaction tube furnace, and heated at 250°C for 5 hours, and further deacidified by argon gas expulsion to obtain a mixed solid of carbon nitride and carbon nitride quantum dots, wherein the flow rate of argon gas is 100 ml / min, and the heating rate of the horizontal reaction tube furnace is 5°C / min; (5) The solid mixture obtained in step (4) was dissolved in deionized water, and ultrasonically dispersed for 15 min using an ultrasonic machine with a power of 200 W, and centrifuged in batches at a high-speed centrifuge of 10,000 rpm for 20 min. The supernatant was ultrasonically dispersed again for 10 min, wherein the centrifugation temperature was 15°C; (6) using a 220 nm microporous filter membrane to perform preliminary filtration on the ultrasonic dispersion obtained in (5), and then using a 25 nm microporous filter membrane to perform secondary filtration on the filtrate; (7) The filtrate obtained by the secondary filtration in step (6) is concentrated by removing water using a rotary evaporator at a rotation speed of 65 rpm, and then placed in a freeze dryer for freeze drying to obtain fluffy carbon nitride quantum dots with high oxygen functional groups, abbreviated as CNQDs, wherein the freezing step is frozen at -60°C for 12 hours, and the vacuum step is operated at a freezing temperature of -60°C for 80 hours; (8) The carbon nitride quantum dots and boron oxide obtained in step (7) were mixed in a mass ratio of 1:1, ground thoroughly, and placed in a small porcelain boat, which was placed in a quartz tube of a horizontal reaction tube furnace. The mixture was sintered at 300°C for 3 h under an argon atmosphere, wherein the argon flow rate was 70 ml / min and the heating rate of the horizontal reaction tube furnace was 5°C / min; (9) The sintered product is ground thoroughly to obtain boron-doped carbon nitride quantum dots, denoted by BCNQDs300 (the number indicates the sintering temperature), which is a solid-liquid dual-state luminescent material.

[0028] 1. The BCNQDs and CNQDs powders obtained in Examples 1-3 were analyzed by TEM transmission electron microscopy and HR-TEM high-resolution transmission electron microscopy. From Figure 1a, c, it can be seen that the particle size ranges of CNQDs and BCNQDs400 are about 2 to 2.68 nm and 2.4 to 3.1 nm, respectively. After calculation, the average particle sizes of CNQDs and BCNQDs400 are 2.34 nm and 2.32 nm, respectively. The particle size morphology of BCNQDs is uniform and the size is controllable, generally about 2 to 4 nm. Figure 1 High-resolution TEM (HRTEM) in b and d shows that the interplanar spacing of both is 0.182 nm, corresponding to the (023) crystal plane of nitrided graphene carbon.

[0029] 2. The BCNQDs and CNQDs powders obtained in Examples 1-3 were analyzed by FT-IR Fourier transform infrared spectroscopy. Figure 1 In Figure e, it can be clearly seen that the absorption peaks of CNQDs and BCNQDs are similar, ranging from 2900 to 3300 cm -1 The broad absorption band at 3020 cm-1 can be attributed to the stretching vibration of OH / NH, while the sharp peak is attributed to the stretching vibration of the terminal amino group (NH). -1 The stretching vibration peak at 3220 cm -1 This indicates that the hydrogen bonds weaken or break with the increase of temperature, and the surface functional groups undergo certain changes. -1 and 1050cm -1 and 1397 cm -1The vibration absorption band at 1718cm is attributed to the stretching vibration peaks of triazine ring, CO and CN, indicating that BCNQDs still retain the characteristic structure of triazine ring. -1 and 1778cm -1 The vibration absorption band at 1781 cm is caused by the stretching vibration peaks of C=N and C=O. -1 The C=O vibration absorption band at 1718cm -1 The C=N vibration absorption band at 923 cm -1 、1110cm -1 、1187cm -1 , and 1432cm -1 New bands are shown at , which can be attributed to BNO, BO, NO and NB stretching, respectively.

[0030] 3. The BCNQDs and CNQDs powders obtained in Examples 1-3 were subjected to UV-vis absorption spectroscopy analysis. Figure 1 f, through the light absorption performance of CNQDs and BCNQDs test samples in the solid state, it can be clearly seen that the absorption edge of BCNQDs is blue-shifted compared with CNQDs. This is because the introduction of NO and NB bonds destroys the conjugated structure of CNQDs and reduces the conjugation, resulting in changes in the band structure and a decrease in the band gap. In addition, the absorption peak of BCNQDs at 220nm can be attributed to the π-π* transition in the sp2-π conjugated domain, while the weak shoulder peak near 285nm is the n-π* transition in C=N / C=O. The UV-Vis absorption spectrum also confirms that the structure of the tri-s-triazine ring is still retained in BCNQDs. Interestingly, as the reaction temperature increases, the broad peak of 330-540nm gradually widens. We believe that this is due to the presence of NO and the coupling of the defect state generated by doping with the conjugated domain, which makes the n-π* transition have a wider energy distribution.

[0031] 4. X-ray photoelectron spectroscopy (XPS) analysis was performed on the BCNQDs and CNQDs powders obtained in Examples 1-3. Figure 1 g, showing that the original CNQDs and BCNQDs contain the main elements: C, N, O and C, N, O, B, respectively.

[0032] 5. The BCNQDs powder obtained in Examples 1-3 was subjected to fluorescence spectrum (PL) and phosphorescence spectrum analysis. Figure 2The study of a, b, and c found that the fluorescence (blue line) and RTP (green line) emission wavelengths of BCNQDs200 are 415nm and 465nm, respectively, and the corresponding excitation wavelength is 305nm. The fluorescence and RTP emission wavelengths of BCNQDs300 are 370nm and 481nm, respectively, and the corresponding excitation wavelength is 290nm. The fluorescence and RTP emission wavelengths of BCNQDs400 are 365nm and 402nm, respectively, and the corresponding emission wavelength is 290-325nm.

[0033] 6. The BCNQDs powder obtained in Examples 1-3 was analyzed for long-life luminescence (phosphorescence) and short-life luminescence (fluorescence) at different excitation wavelengths. Figure 2 g, h, It is found that the phosphorescence emission color of BCNQDs changes with the excitation wavelength. When the excitation wavelength changes from 300nm to 395nm, BCNQDs show a change from blue to green. Under 365nm ultraviolet light, BCNQDs all emit blue-white light. After turning off the light, they show afterglow at 470nm (BCNQDs400), 507nm (BCNQDs300) and 520nm (BCNQDs200), corresponding to Figure 2 The CIE coordinates in h are BCNQDs200 (0.29, 0.43), BCNQDs300 (0.25, 0.38), and BCNQDs400 (0.24, 0.31).

[0034] 7. The BCNQDs400 solution obtained in Example 1 was subjected to fluorescence spectrum (PL) and CIE colorimetric analysis. Figure 2 i. Excitation-dependent photoluminescence was found in the liquid state, and different excitation bands showed emission peaks of different colors. Among them, BCNQDs400 showed three different liquid colors of blue-purple, dark blue and cyan under excitation of 265, 365, and 395nm, respectively.

[0035] 8. The photophysical excitation dependence characteristics of BCNQDs400 prepared in Example 1 were analyzed. Figure 3 As shown, Figure 3 a, b, and c are the solid-state fluorescence, solid-state phosphorescence, and liquid-state fluorescence emission spectra of BCNQDs400 under different excitations, respectively; Figure 3 d, e, and f are the normalized emission spectra of solid-state fluorescence, solid-state phosphorescence, and liquid-state fluorescence of BCNQDs400 under different excitations, respectively.

[0036] like Figure 3 As shown in a, 3d, it can be clearly seen that the fluorescence of BCNQDs400 in the solid state shows an excitation dependence from 370nm to 505nm under an excitation wavelength of 300nm-450nm; while the solid-state phosphorescence is as Figure 3 b, as shown in Figure 3e, under the excitation wavelength of 250nm-400nm, it shows the excitation dependence of 365nm-508nm; Figure 3 c, 3f show the PL fluorescence characteristics of BCNQDs400 in deionized water solution. It can be clearly seen that the excitation-dependent characteristics are still preserved in the liquid environment. The sample shows excitation-dependent characteristics from 410nm to 580nm under 250nm-530nm excitation.

[0037] The solid-liquid dual-state luminescent material prepared by the invention is applied in fields such as anti-counterfeiting and coded information encryption.

[0038] (1) Applied to encrypt coded information, see Figure 4 : The corresponding photographs of BCNQDs400, BCNQDs200 and BCNQDs300 powders prepared in Examples 1-3 under sunlight, 365 nm ultraviolet light and no excitation are as follows: Figure 4 As shown in a, the solid powder will emit fluorescence of different colors under the irradiation of ultraviolet light, and after the ultraviolet light is turned off, there will be a phosphorescence afterglow phenomenon that lasts up to about 12 seconds.

[0039] The BCNQDs400, BCNQDs200 and BCNQDs300 powders prepared in Examples 1-3 were placed in different scale grooves to obtain an initial signal of 8888, such as Figure 4 As shown in Figure b, when irradiated with 365nm ultraviolet light, all BCNQDs emit blue-white light to obtain white signal 8888. After turning off the ultraviolet light, the phosphorescence signal 8888 can still be obtained 1s later. At 5s, the BCNQDs200 sintered at 200℃ has a short life span and will completely stop emitting light. The timetable signal obtained at 5s-7s becomes 4936. At 7s-13s, only the BCNQDs400 sintered at 400℃ has a longer life span and still emits phosphorescence. At this time, another signal 1475 is obtained on the timetable. The above results show that BCNQDs have good application value in information encryption and anti-counterfeiting.

[0040] (2) Anti-counterfeiting identification of products: The BCNQDs400 prepared in Example 1 was dissolved in PVA and mixed to form a two-dimensional code image of Guangxi Normal University.

[0041] When the QR code is illuminated by a 365nm ultraviolet lamp, it emits a bright white glow. After the UV lamp is turned off, the QR code emits a long, clear cyan afterglow. The information characteristics of the QR code can still be read after 12 seconds. This provides feasibility for the first-level anti-counterfeiting information display.

[0042] (3) Anti-counterfeiting ink: The BCNQDs400 prepared in Example 1 has a luminescence-dependent luminescence characteristic in its aqueous solution. The liquid BCNQDs400 is evenly applied on the filter paper and allowed to dry naturally. Figure 4 As shown in Figure c, it can be seen that the pattern on the filter paper shows blue-purple, dark blue, and cyan patterns as it is irradiated with light of different excitation wavelengths. This phenomenon proves the feasibility of its application in anti-counterfeiting inks.

Claims

1. A high quantum yield solid-liquid dual-state luminescent material, characterized in that: The luminescent material is boron-doped carbon nitride quantum dots, abbreviated as BCNQDs in English. The quantum dot solid powder emits bright white light under the irradiation of 365nm ultraviolet lamp; The solid powder was dispersed in water to form a colorless and transparent solution, which showed three different colors of fluorescence, blue-purple, dark blue, and cyan, respectively, under 265nm, 365nm, and 395nm ultraviolet light irradiation, and showed a 15-second afterglow under 365nm ultraviolet light excitation; The quantum dots exhibited a photoluminescence quantum efficiency of up to 15.79% under 365 nm ultraviolet light excitation.

2. The use of the high quantum yield solid-liquid dual-state luminescent material according to claim 1, characterized in that: The luminescent material boron-doped carbon nitride quantum dots are applied in the fields of anti-counterfeiting two-dimensional codes, anti-counterfeiting inks and coded information encryption.

3. The method for preparing the high quantum yield solid-liquid dual-state luminescent material according to claim 1, characterized in that: The luminescent material is boron-doped carbon nitride quantum dots, and the preparation method comprises the following steps: (1) Preparation of carbon nitride powder using melamine as raw material; (2) using the carbon nitride powder prepared in step (1) as a raw material and concentrated nitric acid as a strong oxidant, mixing the two and then oxidizing and refluxing to obtain a mixed solution; (3) diluting the mixed solution obtained in step (2) with deionized water and performing preliminary deacidification treatment using a rotary evaporator; (4) placing the mixed solution that has undergone preliminary deacidification treatment in a horizontal reaction tube furnace for heating, and further deacidifying by using an argon gas expulsion method to obtain a solid mixture; (5) dissolving the solid mixture of step (4) in deionized water, ultrasonically dispersing, and centrifuging in batches using a high-speed centrifuge, taking the supernatant and ultrasonically dispersing it again to obtain an ultrasonic dispersion; (6) Using a 220 nm microporous filter membrane to perform preliminary suction filtration on the ultrasonic dispersion obtained in step (5), and then using a 25 nm microporous filter membrane to perform secondary suction filtration on the filtrate; (7) The filtrate obtained by secondary filtration in step (6) is concentrated by removing water using a rotary evaporator, and then placed in a freeze dryer for freeze drying to obtain fluffy carbon nitride quantum dots with high oxygen functional groups, abbreviated as CNQDs; (8) Grinding the obtained carbon nitride quantum dots and boron oxide mixture thoroughly and placing it in a small porcelain boat, placing it in a quartz tube of a horizontal reaction tube furnace, and performing high-temperature sintering heat treatment in an argon atmosphere; (9) The product sintered in step (8) is ground thoroughly to obtain boron-doped carbon nitride quantum dots, abbreviated as BCNQDs, i.e., solid-liquid dual-state luminescent materials.

4. The preparation method according to claim 3, characterized in that: The step (1) of preparing carbon nitride powder is to place melamine in a muffle furnace, heat it to 500-600°C at a heating rate of 1°C / min-5°C / min, and calcine it for 2-4h to obtain carbon nitride sintered into yellow blocks, and grind the blocks into powder for later use.

5. The preparation method according to claim 3, characterized in that: In step (2), the carbon nitride powder is mixed with concentrated nitric acid at a solid-liquid ratio of 1 g: 100-150 ml, the mass fraction of concentrated nitric acid is 63-68%, the oxidation reflux temperature is 135-150° C., and the reflux time is 24-28 h.

6. The preparation method according to claim 3, characterized in that: The amount of deionized water used in step (3) is 1.5-3 times the volume of the mixed solution after reflux in step (2), the speed of the rotary evaporator is 60-70 rpm, and the deacidification treatment is carried out in a water bath at 80-90° C. for 3-6 preliminary deacidification treatments.

7. The preparation method according to claim 3, characterized in that: In step (4), the flow rate of argon gas is 80-100 ml / min, the heating rate of the horizontal reaction tube furnace is 5°C / min, and the temperature is raised to 200-250°C for 3-5 hours.

8. The preparation method according to claim 3, characterized in that: The power of the ultrasonic machine used for the ultrasonic dispersion in step (5) is 200W, and the ultrasonic dispersion time is 10-15min; the centrifugal speed of the centrifuge is 10000-12000rpm, the centrifugal time of each time is 10-20min, and the centrifugal temperature is 15°C.

9. The preparation method according to claim 3, characterized in that: The rotation speed of the rotary evaporator in step (7) is 60-70 rpm, and freeze drying is performed at -60±10°C for 8-12 hours, and then the water is sublimated according to the set vacuum program. The freezing temperature in the vacuum program is -60±10°C, and the operating time is 60-80 hours.

10. The preparation method according to claim 3, characterized in that: In step (8), the mass ratio of the carbon nitride quantum dots to the boron oxide is 1:1, the flow rate of the argon gas is 60-80 ml / min, the heating rate of the horizontal reaction tube furnace is 5°C / min, and the temperature is raised to 200°C-400°C for sintering heat treatment for 2-5h.

Citation Information

Patent Citations

  • Preparation method of doped carbon nitride fluorescent quantum dots

    CN105670620A

  • Preparation method of amorphous boron-doped graphite phase carbon nitride quantum dot, quantum dot prepared by same and application of quantum dot

    CN112897485A

  • Method for macroscopically preparing carbon nitride quantum dots

    CN113816347A

  • Preparation method and application of amorphous boron-doped carbon nitride

    CN115007194A

  • Preparation method of blue light boron carbon nitrogen quantum dots with high quantum yield

    CN118834688A